Optimalisasi Rehabilitasi Medis kepada Penyalahgunaan Narkotika Di Balai Pemasyarakatan (BAPAS) Kelas 1 Jakarta Barat dan BNN Jakarta Utara Guna Mengatasi Overkapasitas - Allyssa, Allyssa; Adhari, Ade (LPPM Universitas Ekasakti Padang, 2024)
The rehabilitation system for narcotics abusers is implemented in correctional institutions, based on the provisions of Law of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics serves as the legal basis for the prevention and combating of drug abuse in Indonesia. Despite the government's vigorous efforts through the National Narcotics Agency (BNN) This research aims to understand and analyze optimization in rehabilitation, the factors that cause rehabilitation to fail for addicts and victims of narcotics abuse. as well as to understand and analyze the efforts made so that rehabilitation of addicts and victims of narcotics abuse can be carried out to address this issue, drug abuse is estimated to affect 3.8 to 4.1 million people. This research adopts a field research approach with a socio-legal juridical perspective. In the context of overcrowding, the study highlights its impact on rehabilitation programs and emphasizes the importance of a holistic approach. In-depth analysis indicates that limited prisoner access to adequate services can hinder the effectiveness of rehabilitation programs. The integration of criminal law policy theory, prisonization theory, and rehabilitation theory becomes crucial in designing holistic and targeted solutions. Based on the research analysis, it can be concluded that overcrowding creates pressure on human resources, impedes rehabilitation programs, and potentially harms the well-being of prisoners. A profound understanding of criminal law policy theories, including prevention, punishment, rehabilitation, deterrence, utilitarianism, and restorative justice, forms the foundation for formulating policies that guide prisoners not only toward punishment but also towards recovery and social reintegration.